2002
DOI: 10.1080/pdp.21.3.343.352
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Myocardial Necrosis: A Distinctive Cardiac Lesion in Cystic Fibrosis, Lipomatous Pancreatic Atrophy, and Keshan Disease

Abstract: Multifocal myocardial necrosis (MMN) is an unusual cardiomyopathy of childhood, characterized by multiple patchy areas of myocardial fiber necrosis/fibrosis involving mainly the middle part of the left ventricle, but also, to a lesser extent, the right ventricle and the atria. These necrotic lesions are isolated and are not accompanied by an inflammatory reaction or vascular alterations. They are responsible for acute cardiac failure. MMN lesions are observed in various pathologic conditions including cystic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…Nonetheless, comprehensive autopsies of young CF patients have documented pronounced cardiac abnormalities, including left ventricular enlargement and a distinctive histological presentation termed multifocal myocardial fibrosis (MMF) ( 6 , 7 ). Similar cardiac histological patterns have been observed in individuals with severe malabsorption disorders ( 8 ), and intriguingly, in cases of Keshan disease ( 9 ) —a region-specific cardiomyopathy in parts of China predominantly affecting children and pregnant females, linked to selenium deficiency, and largely eradicated following Se supplementation in at-risk groups ( 10 – 12 ).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Nonetheless, comprehensive autopsies of young CF patients have documented pronounced cardiac abnormalities, including left ventricular enlargement and a distinctive histological presentation termed multifocal myocardial fibrosis (MMF) ( 6 , 7 ). Similar cardiac histological patterns have been observed in individuals with severe malabsorption disorders ( 8 ), and intriguingly, in cases of Keshan disease ( 9 ) —a region-specific cardiomyopathy in parts of China predominantly affecting children and pregnant females, linked to selenium deficiency, and largely eradicated following Se supplementation in at-risk groups ( 10 – 12 ).…”
Section: Introductionsupporting
confidence: 57%
“…Nezelof et al ( 8 ) previously identified MMF in 16 instances from an extensive collection of necropsy studies in children younger than two years. Over two decades later, the same researchers noted a resemblance between this fibrosis pattern and Keshan disease, suggesting a shared nutritional deficit as the etiological basis ( 9 ). More recently, selenium deficiency has been linked to Keshan disease, and dietary selenium supplements have proven instrumental in its mitigation and prevention ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selen-Mangelerscheinungen sind bisher bei schweren chronischen Krankheiten beschrieben worden, die auch den Magen-Darm-Trakt betreffen; zum Beispiel langdauernde parenterale Ernährung (etwa bei Morbus Crohn [13], "Short Bowel Syndrom" nach operativer Entfernung eines grossen Teils des Darms [14,15], chronischer Pankreatitis [16], Phenylketonurie [17] oder bei zystischer Fibrose [18].…”
Section: Selenmangelunclassified